Chronic fatigue in Ehlers–Danlos syndrome—Hypermobile type. Issue 1 (10th February 2017) - Hakim, Alan; De Wandele, Inge; O'Callaghan, Chris; Pocinki, Alan; Rowe, Peter
Abstract : Chronic fatigue is an important contributor to impaired health‐related quality of life in Ehlers–Danlos syndrome. There is overlap in the symptoms and findings of EDS and chronic fatigue syndrome. A proportion of those with CFS likely have EDS that has not been identified. The evaluation of chronic fatigue in EDS needs to include a careful clinical examination and laboratory testing to exclude common causes of fatigue including anemia, hypothyroidisim, and chronic infection, as well as dysfunction of major physiological or organ systems. Other problems that commonly contribute to fatigue in EDS include sleep disorders, chronic pain, deconditioning, cardiovascular autonomic dysfunction, bowel and bladder dysfunction, psychological issues, and nutritional deficiencies. While there is no specific pharmacological treatment for fatigue, many medications are effective for specific symptoms (such as headache, menstrual dysfunction, or myalgia) and for co‐morbid conditions that result in fatigue, including orthostatic intolerance and insomnia. Comprehensive treatment of fatigue needs to also evaluate for biomechanical problems that are common in EDS, and usually involves skilled physical therapy and attention to methods to prevent deconditioning. In addition to managing specific symptoms, treatment of fatigue in EDS also needs to focus on maintaining function and providing social, physical, and nutritional support, as well as providing on‐going medical evaluation of new problems and review of new evidence about proposed treatments. © 2017 Wiley Periodicals, Inc.